Desarrollo de un dispositivo portátil texto-voz para personas no videntes para la biblioteca de la Universidad Politécnica Salesiana. - Burga Caza, Daniel Miguel (2018)
Currently people without disabilities require written documents in Braille for reading that may need these documents in a Braille language, but due to its high cost it is not possible to access the information required by the blind person. This is an impediment in access to documents such as books, magazines, newspapers, etc. In the library of the establishment (UPS), there is a group of people without papers who work with commercial software, It is a reader of personal computer screens (PC), which allows them to carry out their work occupations in the institution, but this Software has its limits that require Internet connection to perform the respective updates of the system, in addition the person is not qualified to handle this software. A device was designed and implemented that allowed the group of blind people in the library of that type to listen to the text of books in that way, access texts available in the library and, in addition, they preferred. It was established that the device is portable and easy to use according to the survey made to the non-voters of the UPS library, with the results obtained from the net present value (NPV), and the internal rate of return (IRR). Determined that the cost of the device can be recovered in a time of 4 months.